Analisis Faktor-Faktor Yang Mempengaruhi Literasi Keuangan Pada Petani Tanaman Pangan dan Holtikultura di Kabupaten Maros Sulawesi Selatan - Anas Iswanto Anwar; Rezki Putri; Sabir Sabir (UPT Penerbitan Universitas Jember, 2020)
This study aims to determine the effect of demographic characteristics on the level of financial literacy of food crops and horticulture farmers in Camba sub-district in South Sulawesi Province. This research data obtained from the questionnaire (primary) and few observations and direct interviews with Camba sub-district farmers. This study uses a multiple linear regression analysis method. The results of the analysis concluded that the demographic characteristic variables consisting of income level, age, education level, risk preference dummy, and distance to financial institutions simultaneously had a significant effect on financial literacy variables with a five percent significance level. Income level, education level, risk preference partially had a positive and significant effect on the variable financial literacy. Distance to financial institutions had a negative and significant effect while age doesn’t have a significant effect on financial literacy. Of 43.8 percent from the variation in financial literacy variables is explained by the independent variables used in this model, while the rest of 56.2 percent is explained by other variables.